2012
DOI: 10.1111/j.2042-3292.2012.00431.x
|View full text |Cite
|
Sign up to set email alerts
|

Uterine B cell lymphoma in a mare

Abstract: SummaryIn this report, we describe the diagnostic findings and outcome of a uterine B cell lymphoma in a mare. A well circumscribed uterine mass with significant peripheral vascularisation was identified by transrectal ultrasonography during the reproductive examination of an 8-year-old Thoroughbred mare. Subsequent hysteroscopy revealed that the uterine mass was located intramurally and contained a protruding polyp-like structure. A diagnosis of uterine B cell lymphoma was established by histopathological exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Lymphoma most frequently involves lymphoid, abdominal and thoracic organs followed by skin (Meyer et al 2006) but cases have also been described in the uterus (Claes et al 2015), and limbs (Moser et al 2014). In one study of gastrointestinal neoplasia in the horse, lymphoma was the most common diagnosis (Taylor et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Lymphoma most frequently involves lymphoid, abdominal and thoracic organs followed by skin (Meyer et al 2006) but cases have also been described in the uterus (Claes et al 2015), and limbs (Moser et al 2014). In one study of gastrointestinal neoplasia in the horse, lymphoma was the most common diagnosis (Taylor et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Uterine lymphomas have been described uncommonly in other animal species (Tanaka et al 2003;Burton et al 2010;Claes et al 2015;Diaz-Delgado et al 2015), and in cattle they are most commonly found in association with the bovine leukaemia virus (Olson and Baumgartener 1976;Burton et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, an endometrial fibrosarcoma with invasion in the myometrium; tumor cell emboli in lymphatics; and metastases in lungs, liver, and spleen is described in an 18-year-old Warmblood mare [91]. Other published neoplasms with involvement of the endometrium are multicentric lymphosarcomas, i.e., T-cell lymphosarcoma in a 22-year-old pony mare [92] as well as B-cell lymphosarcomas in a 5-year-old Quarter horse mare [93] and an 8-year-old Thoroughbred mare [94].…”
Section: Endometrial Cancer: a Rare Disease In Maresmentioning
confidence: 99%